Pengaruh Reward, Punishment, Beban Kerja Terhadap Produktivitas Kerja Karyawan (Studi Kasus Pada Pt. Asuransi Jiwasraya Medan Dan Binjai) - Herlianto, Dicky; Aditi, Bunga; Sunaryo, Sunaryo (Universitas Harapan Medan, 2024)
This research was done at PT.Asuransi Jiwasraya North Sumatra with the aim of knowing the effected of reward, punishment and workload on employee work productivity. The population were 128 employees who worked in the company, sampling with saturated samples so that the sample size were 128 respondents. Sources of data using primary data and secondary data and data collection techniques using survey by providing questionnaire. The data analysis technique used data quality test, classic assumption test, and hypothesis test.Based on the results of the study showed that partially reward have significant effected toward employee work productivity, punishment did not have significant effected toward employee work productivity. While workload has significant effect toward employee work productivity at PT. Asuransi Jiwasraya (Persero) North Sumatra. Simultaneously reward, punishment and workload together have significant effected toward employee work productivity at PT. Asuransi Jiwasraya (Persero) North Sumatra. Reward, payment, and workload have moderate correlation with employee work productivity in the company. While the adjusted R2 value = 0.160, meaning that employee work productivity could be explained by reward, payment, and workload amount 16% and the other 84% could be explained by other variables outside the scope of the research that was not carried out.